Drugs in Algeria: a study of the reality of the phenomenon and means of prevention - Bennoui , Aicha (Social Empowerment Journal, 2020)
The study sought to review the reality of the drug phenomenon in Algerian society by shedding light on this phenomenon, which has been witnessing a great development and widespread among the various different groups of society. About drugs in the world within a set of figures and statistics documented about the phenomenon, and the paper revealed the terrible spread of the phenomenon in Algeria and its increasing penetration among segments of society, especially youth groups, through whether related to the quantities seized and the development of the total number of cases dealt with according to the nature of the violation, and the increasing number For addicts, with mentioning the most important prevention mechanisms and means that must be provided to address this phenomenon